ANALISIS BENTUK FUNGSI DAN MAKNA PANTUN MELAYU DALAM SAMBUTAN SEREMONI RESMI - Edward Edward; Sorta Hutahaean (Universitas Lancang Kuning, 2022)
This research was aimed at exploring the meaning, form, and function of Malay poem expression uttered during the official ceremony. The analysis was based on the whole context using an operational approach, that is, how a text works within its context. Out of the form and function, meaning is best viewed from its surrounding context and situation. The result shows that text meaning is context-dependent on the cultural value which operates. The text was found unique because of the subject deletion that takes place. The form of the text may be directive, and yet, it sounds as if it was not. This characteristic is due to suffixing the verb with a particle, “lah”. Thus, the function of the directive form is weakening. It tends to be a very polite request instead of an order. 80% dominates the form of representative and the rest was directive.